Społeczne uwarunkowania transferu wiedzy przy wykorzystaniu Internetu - Komańda, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the case of Internet we can mark out the virtual community with specific network relations between people, that are systematic and integrated by coordinators. This phenomenon together with the technological aspects determine the knowledge transfer. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 446-451